(3CSQGQ GdYde HCMcGe GdfLhes - (3CHh Ydj GdTGgOs
(3ChdgG (B:s
(3CeG HYO , aEfi deG LYd YfOi ef CSQGQ Yde GdfLhe ef CbGhjd GdChGFd , hGSJNQLJg HebOGQ WGbJi , CMHHJ Cf CPcQ efgG TjFkG djchf Pdc JPcQI def jHJOF s
(3BNQgG (B:s
(3hHYOg HGdRgQI UGMHI TQa GdMhJ hdgG KeGfi Sfjf aLedJg (B( (3YL (B) (3SfI agPG eG jJHjf dfG ef YdI EaQOGQGJ GdchGcH hJQJjHgG , hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B93 - (3U(B98s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI ceHQL (B_ (3EfLdJQG (B(19_3 9 G) s
Keywords: (3Gdadcs